The Effect of Compensation on Employee Performance in the Islamic Education Division of the Regional Office of the Ministry of Religious Affairs of South Sulawesi Province - Mufida, Mufida; Tawe, Amiruddin; Burhanuddin, Burhanuddin (Entrepreneurship, Management, and Business Research Journal, 2024)
Penelitian ini bertujuan (1) mengetahui dan menganalisis pengaruh pemberian kompensasi Finansial terhadap kinerja pegawai bidang pendididkan agama islam kantor wilayah kementerian agama provinsi sulawesi selatan (2) untuk mengetahui dan menganalisis pengaruh pemberian kompensasi non finansial terhadap kinerja pegawai bidang pendididkan agama islam kantor wilayah kementerian agama provinsi sulawesi selatan (3) mengetahui dan menganalisis pengaruh kompensasi finansial dan kompensasi non finansial secara bersama-sama terhadap kinerja pegawai bidang pendididkan agama islam seluruh pegawai di bidang pendidikan Islam kantor wilayah kementerian agama provinsi sulawesi selatan adalah subjek penelitian ini. Kuesioner disebarkan untuk mengumpulkan data. Teknik analisis data yang digunakan yaitu analisis regresi linear berganda dengan menggunakan Statistical Product Service Solution (SPSS). Hasil penelitian menunjukkan bahwa 1). Terdapat pengaruh positif dan signifikan pada kompensasi finansial terhadap kinerja pegawai di bidang pendididkan agama islam kantor wilayah kementerian agama provinsi sulawesi selatan. 2). Terdapat pengaruh positif dan signifikan kompensasi non finasial terhadap kinerja pegawai pada bidang pendididkan agama islam kantor wilayah kementerian agama provinsi sulawesi selatan 3). Terdapat pengaruh positif dan signifikan pada kompensasi finansial dan kompensasi non finasial secara bersama-sama terhadap kinerja pegawai pada bidang pendididkan agama islam pada Kantor Wilayah Kementerian Agama Provinsi Sulawesi Selatan. This research aims to (1) determine and analyze the effect of providing financial compensation on the performance of employees in the field of Islamic religious education at the regional office of the Ministry of Religion of South Sulawesi Province (2) to find out and analyze the effect of providing non-financial compensation on the performance of employees in the field of Islamic religious education at the regional office of the provincial Ministry of Religion South Sulawesi (3) to find out and analyze the influence of financial compensation and non-financial compensation together on the performance of employees in the field of Islamic religious education at the regional office of the Ministry of Religion of South Sulawesi Province. The population in this study were all employees in the field of Islamic religious education at the regional office of the Ministry of Religion, South Sulawesi Province. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression analysis using Statistical Product Service Solution (SPSS). The research results show that 1). There is a positive and significant influence on financial compensation on employee performance in the field of Islamic religious education at the regional office of the Ministry of Religion, South Sulawesi province. 2). There is a positive and significant influence of non-financial compensation on employee performance in the field of Islamic religious education at the regional office of the Ministry of Religion, South Sulawesi Province 3). There is a positive and significant influence on financial compensation and non-financial compensation together on the performance of employees in the field of Islamic religious education at the regional office of the Ministry of Religion, South Sulawesi province.